Sierra Leone : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1997)
This paper reviews economic developments in Sierra Leone during 1994-96. The disruption to agriculture at the start of the rebel war precipitated negative growth in 1991/92 and 1992/93. The relatively peaceful conditions that prevailed in 1993/94 brought a rebound in agriculture as well as in diamond mining activities. As a result, real GDP grew by an estimated 5 percent. The turnaround was cut short in 1994/95 with the escalation of rebel attacks and amid closure of rutile and bauxite mining operations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet